Evaluation of a research methods course for clinical residents - Maryamalsadat Kazemi Shishavan; Mahasti Alizadeh (Tabriz University of Medical Sciences, 2019)
Background: Residency programs generally carry out various educational interventions to improve residents' publication records. Since an intervention may not produce the same effect in different locations, evaluating the effectiveness of individual interventions is essential for examining progress in this field of study. Authorities at the Tabriz University of Medical Science (TUOMS) proposed a research training program targeting a rise in residents' scholarly activity and publications; this study aimed to evaluate the program and share the findings and experiences. Methods: Questionnaires were sent to 182 residents and the heads of all clinical departments. Evaluators used Kirkpatrick's four-level model and Stufflebeam's Context, Input, Process and Product model for data gathering and analyzing. Focus group discussions (FGDs) and in-depth semi-structured interviews were done with faculty members, executive staff, and residents to complement the survey results. Data were summarized and categorized using quantitative and qualitative analysis. Results: The participation rate for residents and heads of departments were 76 (41.7%) and 14(70%), respectively. At the end of the course, residents assessed their knowledge and research skills as weak or medium in most of the subjects. A total of 182 (100 %) residents prepared thesis proposals. Only 82 (49.1%) residents completed their thesis, and 19 (11.3%) published papers.Generally, participants were not satisfied with the course. Barriers noted were: mandatory topics for theses, an intensive course with a one-month duration, a lack of consideration of practical subjects, high cost of the course, and failure to achieve an increase in publications. Conclusion: The Self-assessment results of increased knowledge and research skills did not indicate improvement. Mandatory participation in the course did not result in the expected publication increase.